About the Cosmological Constant, Acceleration Field, Pressure Field and Energy - Sergey G. Fedosin (Jordan Journal of Physics, 2025)
Based on the condition of relativistic energy uniqueness, the calibration of the cosmological constant was performed. This allowed to obtain the corresponding equation for the metric and to determine the generalized momentum, the relativistic energy, momentum and mass of the system, as well as the expressions for the kinetic and potential energies. The scalar curvature at an arbitrary point of the system equaled zero, if the matter is absent at this point; the presence of a gravitational or electromagnetic field is enough for the space-time curvature. Four-potentials of the acceleration field and pressure field, as well as tensor invariants determining the energy density of these fields, were introduced into the Lagrangian in order to describe the system’s motion more precisely. The structure of the Lagrangian used is completely symmetrical in form with respect to the fourpotentials of gravitational, electromagnetic, acceleration and pressure fields. The stressenergy tensors of the gravitational, acceleration and pressure fields are obtained in explicitform . Each of them can be expressed through the corresponding field vector and additional solenoidal vector. A description of the equations of acceleration and pressure fields is provided. Keywords: Cosmological constant, Acceleration field, Pressure field, Covariant theory of gravitation.